Modulation of Increased mGluR1 Signaling by RGS8 Protects Purkinje Cells From Dendritic Reduction and Could Be a Common Mechanism in Diverse Forms of Spinocerebellar Ataxia - Wu, Qin-Wei; Kapfhammer, Josef P. (Frontiers in Cell and Developmental Biology, 2021)
Spinocerebellar ataxias (SCAs) are a group of hereditary neurodegenerative diseases which are caused by diverse genetic mutations in a variety of different genes. We have identified RGS8, a regulator of G-protein signaling, as one of the genes which are dysregulated in different mouse models of SCA (e.g. SCA1, SCA2, SCA7 and SCA14). In the moment, little is known about the role of RGS8 for pathogenesis of spinocerebellar ataxia. We have studied the expression of RGS8 in the cerebellum in more detail and show that it is specifically expressed in mouse cerebellar Purkinje cells. In a mouse model of SCA14 with increased PKCγ activity RGS8 expression was also increased. RGS8 overexpression could partially counteract the negative effects of DHPG-induced mGluR1 signaling for the expansion of Purkinje cell dendrites. Our results suggest that the increased expression of RGS8 is an important mediator of mGluR1 pathway dysregulation in Purkinje cells. These findings provide new insights in the role of RGS8 and mGluR1 signaling in Purkinje cells and for the pathology of SCAs.